Exploring Race, Culture, and Family in the Identities of Mixed Heritage Students. Issue 3 (2nd July 2016) - Johnston-Guerrero, Marc P.; Pecero, Veronica
Abstract : Family plays an integral role in racial and cultural socialization, yet how mixed heritage students understand the concepts of race and culture in relation to family is unclear. This qualitative study explored the interplay of race, culture, and family in the identity constructions of 25 mixed heritage students. Findings suggest the centrality of culture to identity and that family provides limited sources of racial and cultural knowledge useful for navigating monoracial environments.